TEACHING READINESS AND SPIRITUAL GROWTH OF THE LEARNERS AMONG PAROCHIAL SCHOOLS IN THE ARCHDIOCESE OF JARO - Sarduma, Gemma Flores (IDEAS: Journal of Management & Technology, 2025)
The study used descriptive-correlational method. It aimed to determine the relationship between the degree of teaching readiness and level of spiritual growth of the learners among parochial schools in the archdiocese of Jaro. The participants in this study were the one hundred and sixty-six (166) elementary, and junior high school Christian living teachers among parochial schools in the Archdiocese of Jaro. Data were gathered through a researcher-made questionnaire. Results of the study revealed that teaching readiness was high and the level of spiritual growth of the learners was high. There were no significant differences in the degree of teaching readiness of Christian living teachers when respondents were grouped according to selected profile. There were no significant differences in the learners' spiritual growth level when grouped according to selected profile. A significant relationship was found between the degree of teaching readiness of Christian living teachers and the level of spiritual growth of the learners. The results of this study will help the School administrators of parochial schools as reference information for effective and efficient management and maneuvering of the curriculum as well as to teachers to improve their skills in instilling knowledge and enhancing the spiritual growth of the learners.